Enhancing Digital Literacy Through the Introduction of Robotics and Scratch for Primary School Students in Kedah, Malaysia - Lukman Syafie; Herman Herman; Ihwana As'ad; Anita Badriah (Mattawang: Jurnal Pengabdian Masyarakat, 2025)
This community service program aims to improve digital literacy among elementary school students in Kedah, Malaysia through introducing robotics and Scratch programming. The main issue faced was students' limited exposure to computational thinking and STEM-based learning. Through intensive training provided by Universitas Muslim Indonesia, students from 13 schools were equipped with fundamental skills in visual programming using Scratch and basic robotics concepts. The training was officially opened by the Special Officer to the Minister of Education Malaysia and covered introduction to computational thinking, hands-on Scratch programming, and educational robotics demonstrations. Results showed significant improvement in students' understanding of programming concepts and increased enthusiasm towards technology. Additionally, an educational module was created for continued learning. The program successfully enhanced students' digital literacy and received strong appreciation from school principals who expressed interest in ongoing collaboration for similar activities.